Zebularine significantly sensitises MEC1 cells to external irradiation and radiopharmaceutical therapy when administered sequentially in vitro. (9th December 2013) - Bryan, Jeffrey N.; Kumar, Senthil R.; Jia, Fang; Balkin, Ethan R.; Lewis, Michael R.
Abstract Zebularine is a cytidine analogue incorporated into DNA during replication, inhibiting DNA methyltransferase 1 (DNMT1), resulting in demethylation and changes in gene expression. Such modification may improve radiosensitivity in resistant lymphoma cells. The hypothesis of this study was that zebularine and radiation would synergistically inhibit cell growth and viability. Human MEC1 malignant B cells were incubated with 0–200 µM zebularine for 48 h. Media containing zebularine was removed, and the cells were irradiated with 0–2 Gy of either external beam irradiation or 177Lu‐DOTA‐TATE, a radiolabelled somatostatin analogue. Concentration and viability were measured over 48–72 h. The proportion of apoptotic cells was identified using an active Caspase 3/7 assay. Zebularine inhibited growth of cells in a dose‐dependent manner during exposure. No residual growth inhibition occurred following removal of the drug. Zebularine and external irradiation inhibited cell proliferation in a dose‐dependent, synergistic interaction, but the effect on viability was additive. Treatment with zebularine and 177Lu‐DOTA‐TATE resulted in less inhibition of proliferation (P = 0.0135), but a synergistic decrease in viability. Apoptotic fraction was much higher in cells irradiated with 177Lu‐DOTA‐TATE than external irradiation. External irradiation induces growth arrest rather than apoptosis. Apoptosis is the primary effect of radiopharmaceutical therapy on tumour cells. Treatment with the methylation inhibitor, zebularine, appears to synergistically augment these natural effects in vitro, which could be exploited clinically.